The effect of customer satisfaction and employee satisfaction on business performance - BENSHINA, Khaled (Zenodo, 2022)
Abstract Background: This paper points to evidence of a relationship between employee satisfaction, business performance, and its role in improving customer satisfaction in Libyan hotels. Objectives: this study aims to know the relationship between employee satisfaction, business performance, and customer satisfaction , and its role in improving customer satisfaction in Libyan hotels. Method: We studied four and five-star hotels in Libya. The Statistical Package for Social Sciences (SPSS) was used to analyze the survey data, factor analysis, and correlation analysis to reveal the relationship between study variables. Results: There is a statistically significant relationship between the study variables to improve customer satisfaction. Conclusion: From this study, the author concluded that the hotel industry in Libya should diagnose the main factors that cause employee happiness. Hotels should increase their concern for employee welfare to enhance their sense of belonging and reinforce their commitment. Because motivating them will have a positive effect on customer satisfaction.
Keywords: employee satisfaction, customer satisfaction , business performance, hotel industry